Optimalisasi Digital Banking: Upaya Meminimalisir Risiko Teknologi Informasi - Lestari, Enny Puji; Lydia putri, Nyimas; Zulaikha, Siti (Jurnal Keuangan dan Perbankan Syariah, 2025)
Purpose: Thepurposeofthisresearchistoseetheextentofdigitalbanking optimization inBPRSBandarLampungandBPRSMAUSyariah,andeffortstominimizetheriskofinformationtechnologyinBPRSMAUSyariahandBPRSBandarLampungseenfromthebenefitsofdigitizingcustomersatisfaction,aswellasgainingtrustforcustomersandbanks. Design/methodology/approch: The research paradigm used in this research is the interpretive paradigm, with the type of qualitative research. This research study uses Phenomenology This research will explore and understand the optimization of digital banking in an effort to minimize the occurrence of information risks which are further described and narrated. Research Findings: The results of the Optimization Research from BPRS MAU Syariah and BPRS Bandar Lampung, must continue to be improved in understanding and awareness of the importance of bank digitalization, which greatly affects the impact of trust for customers and banks. So that financial stability at BPRS is more increased and the quality of service can have an impact on product loyalty as a sense of satisfaction, a willingness to pay more and an unwillingness to move to another product. The use of information technology whose operations experience risks is due to; (i) weak governance of BPRS technology in the use of digital technology, (ii) the complexity of information technology assets that are not controlled by the needs of systems and human resources where these needs must still be improved so that the value of needs inherent in financial stability can have an impact on customer satisfaction. Keywords: Digital Banking, Information Technology Risks